Integrating Engagement and Interpersonal Bond: Effect on Directed Performance - Akoto, Edward O.; Akoto, Eunice V.; Campbell, Nathanael S.; Jackson, Lonnie L. (American Journal of Management, 2020)
This study integrates the mediating effects of supervisory commitment and job engagement on directed outcomes of citizenship behaviors and task performance in multiple models. Independent, parallel, and serial mediational models were examined using data from supervisor-employee dyads in small-sized firms. Structural equation modeling (SEM) procedure in STATA 15 was used to fit the models and the PROCESS macros was used to validate the relationships. Both tests confirmed the independent and parallel but not the serial mediational model. Supervisory commitment was superior in mediating the effect of organizational commitment on all performance outcomes in the parallel model but not engagement. The results reaffirm the importance of the interpersonal bond and contrast the assumed predictive effect of job engagement.